SWOT ANALYSIS OF FORMAL SCHOOLS INTEGRATED WITH THE ISLAMIC BOARDING SCHOOL EDUCATION SYSTEM (Case Study in Cikanyere Integrated Senior High School, Ciamis Regency) - Maya Mariah Zakiah (Wawasan Pendidikan, 2023)
The formal education system that is integrated with islamic boarding school education is increasingly in demand by the public. This is because formal education based on Islamic boarding school education is in line with the objectives of national education in the form of forming people who have faith and piety, have noble character, are physically and spiritually healthy, capable, knowledgeable and creative, develop independence and become good citizens. The high public demand for formal education based on Islamic boarding schools and the purpose of national education is a strength, opportunity, threat and weakness for Cikanyere Integrated Senior High School. The purpose of this study was to determine the strategic position of Cikanyere Integrated Senior High School with a SWOT analysis. The methods used in the research are qualitative and quantitative research methods. The research object focuses on aspects of learning quality, namely the Input, process, and Output aspects. All data were found through interviews, literature studies, observations, documentation and questionnaires. The results showed that the position of the input aspect was in quadrant II S-T (Strenght-Threats), this position indicates that the Input component is quite strong but faces great challenges. The results of the SWOT analysis on the process components are in quadrant IV negative-negative (Weaknesses-Threats). This position proves the process component is in a weak state and faces great challenges. Meanwhile, the results of the SWOT analysis on the output component produce a strategy in the S-S (Strength-Strenght) quadrant. This position proves that the output component is strong enough and has opportunities. However, the values of X, and Y are very low at only 0.10 and 0.5 points so the position is very volatile.